Neuromuscular control and exercise-related leg pain in triathletes - Chapman, A. R.; Hodges, P. W.; Briggs, A. M.; Stapley, P. J.; Vicenzino, B. (Medicine & Science in Sports & Exercise, 2010)
Previous studies have shown that cycling can directly influence neuromuscular control during subsequent running in some highly trained triathletes. A relationship between this altered neuromuscular control of running and musculoskeletal pain and injury has been proposed; however, this link has not been investigated. Purpose: This study aimed to evaluate the influence of cycling on neuromuscular control during subsequent running in highly trained triathletes with and without exercise-related leg pain (ERLP). Methods: Participants were 34 highly trained triathletes: 10 triathletes with a history of ERLP and 24 training-matched control triathletes with no history of ERLP. Knee and ankle kinematics and leg muscle recruitment were compared between a baseline run (no prior exercise) and a transition run (preceded by cycling; i.e., run vs cycle run). Results: Knee and ankle joint kinematics were not different between baseline and transition runs for any triathletes: absolute mean difference (±95% confidence interval) was 1.49° ± 0.17°. However, muscle recruitment was different between baseline and transition runs, defined by absolute mean difference in EMG amplitude =10%, in 5 of 24 control triathletes (11/130 muscles exhibited altered recruitment) and in 5 of 10 triathletes with a history of ERLP (12/50 muscles exhibited altered recruitment). This represents a relative risk of 2.40 (0.89-6.50; P = 0.089) when defined by athletes and 2.62 (1.34-6.01; P < 0.01) when defined by muscles. The magnitude of change in muscle recruitment between baseline and transition runs was not different between control (14.10% ± 2.34%) and ERLP triathletes (16.31% ± 3.64%; P = 0.41). Conclusions: This study demonstrates an association between ERLP in triathletes and their neuromuscular control when running off the bike.